Covid-19 Pandemic Impact on World Economy - Zunaira Zahoor (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
This study is being conducted when the Corona virus spreads around the world and becomes an economic major crisis in 2020. Researchers explain the impact of the Corona virus on the world economy by getting information from Standard & poverty agencies (S&P), Organization of Economic Cooperation and Development (OECD), and from different websites and reports. moreover, researchers obtain information from the International Monetary Fund (IMF). In addition, Explain the losses from one industry to another and concluded that the global economy is confronted by dual crises in nature. The deaths of millions of people are on the one hand and the economy crisis on the other. The first problem comprises saving people from death, and the second in saving the universe against economic crises. But both challenges are inconsistent. If individuals want to preserve lives, a remain at home and a social distance policy are imposed, and the country is shut down. However, we can rescue our citizens living, but the economy collapses fast because all the companies in the country have been shut down. If economic crisis is saved, people are supposed to go out and work as normal, the global economy would boost but soon millions or billions of people are lost who will also have an impact on the economic downturn. Policymakers, doctors and manufacturers of health should work together to identify solutions to benefit both individuals living and saving economic crisis.